Analisis Muatan Literasi Kritis pada Buku Pembelajaran Bahasa Indonesia Kelas VII SMP - Poppy Aulia Sutarli; Liliana Muliastuti; Siti Ansoriyah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Critical literacy is an essential competency that needs to be developed in Indonesian language learning to meet the demands of twenty-first-century education. Students are expected not only to understand information literally but also to analyze, evaluate, and reflect on various forms of information critically. This study aims to analyze the critical literacy content embedded in the Grade VII Indonesian language textbook used in junior high schools. The research employed a qualitative descriptive approach using content analysis as the primary method. The data source was the revised edition of the Grade VII Indonesian language textbook published by the Ministry of Education, Culture, Research, and Technology of Indonesia. Data were collected through documentation techniques and analyzed based on critical literacy indicators, including comprehension, analysis, evaluation, and reflection. The findings reveal that critical literacy content has been integrated into various learning activities, such as comparing information from multiple sources, identifying fake news (hoaxes), analyzing multimodal texts including posters and infographics, and engaging in reflection and discussion activities. These findings indicate that the textbook supports the development of critical thinking skills and Higher Order Thinking Skills (HOTS). However, the exploration of ideological perspectives, power relations, and sociocultural contexts within texts remains limited and requires further enhancement. Therefore, future textbook development should incorporate deeper dimensions of critical literacy to foster students who are critical, reflective, and responsive to social issues in contemporary society.